The Effect of Zinc (Zn) Micronutrient Supplementation through Seed Priming and Foliar Spray on the Growth and Grain Yield of Several Sorghum Varieties - Nurul Rusdi; Muhammad Kamal; Eko Pramono; M. Syamsoel Hadi; Kukuh Setiawan (Riviera Publishing, 2025)
The nutrient Zn plays an important role as a cofactor of many types of enzymes related to carbohydrate metabolism, protein metabolism, auxin metabolism, pollen formation, integrity maintenance, biological membrane and resistance to certain pathogens so that its robustness can inhibit plant growth and production. The sufficient availability of Zn in plants has a positive effect on increasing the efficiency of photosynthesis, one of which is through the important role of the enzyme Carbonate Anhydrase. This study aims to determine the effect of the application of Zn micronutrients given through seed priming and foliar spray on several varieties of sorghum carried out on the Ultisol sour dry land in Central Lampung. The trial was carried out in May - September 2024 using a three-replication factorial group random design (RAK). The first factor is the type of sorghum varieties, namely Numbu, Samurai 2, Super 2, and Suri 1. While the second factor is Zn treatment in the form of: control, ZnSO4.7H2O 0.5% seed priming application, ZnSO4.7H2O 0.5% seed priming and foliar spray application in the vegetative phase, ZnSO4.7H2O seed priming and foliar spray application 0.5% in the generative phase and seed priming and foliar spray ZnSO4.7H2O 0.5% application in the vegetative + generative phase. The results of the study showed that the difference in varieties had a real effect on vegetative growth and leaf growth. Micronutrient Zn has a significant impact on increasing plant height, leaf width, greenness/chlorophyll level of leaves and seed yield per plant.